2016
DOI: 10.3748/wjg.v22.i19.4673
|View full text |Cite
|
Sign up to set email alerts
|

Steatotic livers are susceptible to normothermic ischemia-reperfusion injury from mitochondrial Complex-I dysfunction

Abstract: Warm IRI impairs steatotic liver Complex-I activity and function. The protective effects of IPC in steatotic livers may not be mediated through mitochondria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
6

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 27 publications
2
13
0
6
Order By: Relevance
“…Although steatotic livers are highly sensitive to injury, some pre‐conditional protocols are also effective in improving mitochondrial function and liver function after hepatic IR injury. Although IPC exerts no effect on mitochondrial function, it significantly normalizes the function of fatty livers . The protective effect of suppressing mitochondrial MPT in pre‐conditional protocols is more significant in young rats than in old rats after hepatic IR injury .…”
Section: Hepatic Ir Exerts Various Effects According To Liver Healthmentioning
confidence: 96%
“…Although steatotic livers are highly sensitive to injury, some pre‐conditional protocols are also effective in improving mitochondrial function and liver function after hepatic IR injury. Although IPC exerts no effect on mitochondrial function, it significantly normalizes the function of fatty livers . The protective effect of suppressing mitochondrial MPT in pre‐conditional protocols is more significant in young rats than in old rats after hepatic IR injury .…”
Section: Hepatic Ir Exerts Various Effects According To Liver Healthmentioning
confidence: 96%
“…Generally speaking, fatty livers are particularly susceptible to IR damage. Animal experimental results have shown that the IR damage mechanism differs between normal and fatty liver [ 38 ]. NFκB subunit p65 activation plays a key role in steatotic liver transplantation-induced IR injury [ 39 ].…”
Section: Underlying Mechanism and Approaches To Treating Hepatic Ir Imentioning
confidence: 99%
“…However, despite some limited improvement in some liver damage biomarkers (ie ATL), the lack of significant positive effect in clinical outcome have so far prevented its translation to the clinical setting, possibly related to the failure to recover the mitochondrial CI activity noted for the steatotic liver following IR [13] and the associated loss in ROS homeostasis.…”
Section: Ischemic-preconditioningmentioning
confidence: 99%